Possibilities of exploitation of secondary deposits (post mining dumping grounds) as an example of changes in extractive industry - Warcholik, Witold; Dolnicki, Piotr; Gawor, Łukasz (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2014)
Polish coal mining industry produces ca. 35 millions Mg of mining wastes per year. There are ca. 250 post - mining dumping grounds in Poland, situated in three coal basins: Upper Silesian Coal Basin, Lower Silesian Coal Basin and Lublin Coal Basin. Post - mining dumping grounds may cause serious environmental hazards. Their negative influence on the natural environment, as well as risks posed to the inhabitants, calls for effective preventative measures. In the paper, presented are distribution and characteristics of post - mining dumping grounds in the Upper Silesian Coal Basin. The most important environmental issues connected with disposing of wastes are discussed. Technical possibilities of recovery of coal from waste dumps as anthropogenic secondary deposits are analyzed. An example of economical justification of recovery of coal from post - mining dumping ground is presented. Also mentioned are legal regulations connected with exploitation of waste dumps.